Yeasts From Xerophilic Environments Reveal Antimicrobial Action Against Fruit Pathogenic Molds. Issue 1 (3rd September 2015) - Oro, Lucia; Ciani, Maurizio; Comitini, Francesca
Abstract: In the present study, we investigated the occurrence of yeast flora in a xerophilic environment, the desert region of Namibia, with the aim to isolate the yeast strains with antimicrobial activity toward plant pathogen molds. Using traditional culture‐dependent methods, a total of 44 yeast strains belonging to 6 genera and 12 species were isolated. The yeast isolated from red berry samples revealed the widest biodiversity, while only C ryptococcus albidus strains were isolated from desert melon and leaf samples. A wide antimicrobial activity toward pathogenic molds was observed in vitro tests for the yeasts belonging to A ureobasidium pullulans (strains F32 and F60), C . albidus (S14) and S accharomyces cerevisiae (RB24). This behavior was confirmed in vivo tests, where A . pullulans  F32 and F60 completely counteracted P enicillium digitatum decay in lemon and orange, respectively, while C . albidus  S14 showed a similar strong antimicrobial effect in both fruits. S.   cerevisiae strain RB24 exhibited a widespread inhibitory activity against M onilinia fructicola on cherries. Practical Applications: To the best of our knowledge, the antimicrobial activity exhibited by selected yeasts from xerophilic environment could be used as a biological practice in postharvest as an alternative biotechnological approach to reduce the use of synthetic fungicides. Indeed, the biological control using antagonistic yeasts offers an alternative approach to combat pathogen molds on fruits and vegetables.